Pengaruh Digital Marketing terhadap Peningkatan Brand Awareness pada Bisnis Online - Noni Antika Khairunnisah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effect of digital marketing on increasing brand awareness in online businesses in Indonesia. The research method used is associative quantitative research with a multiple linear regression approach. Data were collected through an online questionnaire distributed to 120 respondents, namely active consumers who have interacted with online businesses in Jakarta, Bandung, and Surabaya. The results show that social media activities and digital advertising have a positive and significant effect on brand awareness, with t-values of 8.214 and 6.745, respectively (p-value <0.05). The coefficient of determination (R2) of 0.684 indicates that 68.4% of the variation in increased brand awareness is explained by digital marketing factors, while the remaining 31.6% is influenced by other variables outside the model. These findings support the digital marketing theory proposed by Kotler and Keller (2021), which states that effective digital strategies can expand brand reach, increase consumer engagement, and build long-term loyalty. The practical implications of this study suggest that online business actors need to optimize their digital marketing strategies by integrating social media, paid advertising, and creative content relevant to the target market. In addition, consistency of brand identity across various digital platforms is a key factor in increasing consumers’ brand recall. Overall, this study confirms that digital marketing plays an important role as a strategic instrument in building and strengthening brand awareness in the digital economy era.